A COMPARATIVE STUDY RESULTS ON IN-PERSON AND ONLINE SESSIONS OF FALL SEMESTER OF 2020-2021 - Damchaasuren. Kh.; Oyunjargal. Ch.; Otgonbayr. Ts. (International Journal of Innovative Technologies in Social Science, 2022)
It is inevitable that digital transformation and technological advancement in ICT sector brings drastic changes into every aspect of our lives, and it has become top priorities of the countries around the world for the successful utilization into the mode of learning and teaching within the education sector. Though the fall semester of our university started off with regular regulations, all the education services were shut down due to the local transmission of COVID-19 pandemic in Mongolia. To continue the education services to the students during the strict lockdown, the usage of online training approaches through TV, radio and other means of technology were required to be introduced. The purpose of this comparative study is to conduct detailed analysis on the benefits and downsides of both online and in-person training approaches with its impact, and to highlight the key follow-ups for further improvement.